Exposure to Parental Alcohol Use Is Associated with Adolescent Drinking Even When Accounting for Alcohol Exposure of Best Friend and Peers. (24th December 2021) - Smit, Koen; Zucker, Robert A; Kuntsche, Emmanuel
Abstract: Aims: To further disentangle the role of exposure to drinking of role models (parents, peers, best friends) in the development of young adolescent alcohol use, the current study examined (a) whether parent's alcohol use exposure was associated with alcohol use outcomes among adolescents and (b) whether this association remained significant when including best friend and peer drinking exposure. Methods: A longitudinal study followed 765 adolescents from the Netherlands over 3 years. Adolescents (45.6% male, Mage = 11.78, standard deviation = 0.49 at baseline) completed questionnaires every 6 months, resulting in seven measurement waves. Adolescents reported their own alcohol use and exposure to parental, best friend and peers drinking. Results: Multilevel regression analyses indicated that parental alcohol use exposure was positively associated with a higher likelihood of adolescent alcohol use in the past 6 months, drinking in the last month and binge drinking in the last month. These associations remained significant when including exposure to peer and best friend's alcohol use, also when controlling for alcohol use at the previous timepoint (i.e. change in drinking). These associations were also consistent for boys and girls. Conclusions: Throughout early adolescence, parental alcohol exposure matters for their offspring's alcohol use, independently of whether peers or their best friend expose them to alcohol or not. Parental alcohol exposure should be considered in prevention efforts to further decrease the number of adolescents that engage in early alcohol use and binge drinking. Abstract : Short Summary: This longitudinal study followed 765 adolescents from the Netherlands for 3 years. Results indicated that throughout early adolescence, parental alcohol exposure was associated with offspring alcohol use, independently of whether peers or their best friend exposed them to alcohol or not.